Dinâmica de redes genéticas regulatórias do destino celular em resposta a dano ao dna contemplando senescência, autofagia e apoptose - Gupta, Shantanu (2021)
How a cell determines a given phenotype upon damaged DNA is an open problem. Cell fate decisions happen at cell cycle checkpoints and it is becoming clearer that the p53 pathway is a major regulator of cell fate decisions involving apoptosis or senescence upon DNA damage, especially at the G1/S checkpoint. However, recent results suggest that this pathway is also involved in autophagy induction upon DNA damage. In this work, we using logical models that are well-suited to capture salient dynamical properties of regulatory networks. In this formalism, cell fates are associated with model attractors (stable states or cyclic attractors) whose identification and reachability properties are particularly relevant. Therefore, we dedicate attention to logical models on the G1/S cell cycle checkpoint regulation contemplating the role of miR-34a and miR-16 in response to DNA damage. First, we investigate whether the coordinate action between miR-34a and miR-16 can explain experimental results in multiple cell lines of (NSCLC) and (CTCL). For that, we developed a Boolean model of the G1/S checkpoint regulation contemplating the regulatory influences of both miRNAs. From the model analysis, our results suggest that miR-34a is the main controller of miR-16 activity in NSCLC and CTCL. Additionally, we also proposed the first Boolean model of the transfection of miR-16 that can induce a DNA damage response and induced G1/S checkpoint considering the decision between three phenotypes (tristability): apoptosis, senescence, and autophagy in U87 glioblastoma cells. We also predict that the positive feedback involving ATM, miR-16, and Wip1 has an influence on the tristable state. The model predictions were compared to experiments of gain and loss of function in other three different cell lines (MCF-7, A549, and U2OS) presenting outstanding agreement. For p53-deficient cell lines, our model contemplates that the alternative AMPK pathway can compensate for this deficiency. We conclude that the induction of different phenotypes is stochastic in the U87 cell line and others. This thesis provides two new aspects of miRNAs functions, namely the significance of miR-34a that regulates the miR-16 activity and triggers DNA Damage mechanism by the manipulation of miR-16 in cancer cells.